Rhythmicity as an important regulatory factor in complex biological systems: introduction to chronopharmacology - Kalafatakis, Konstantinos (Annals of Research Hospitals, 2018)
Chronobiological discoveries on the importance of circadian and ultradian rhythms in fundamental processes of living systems have managed to unify the seemingly opposing views between Heraclitus (“everything flows”) and Cannon (“stability of the internal environment is a condition for life”). Bio-rhythmicity is an inherent phenomenon of biosystems, created by the interplay among different infra- and supracellular mechanisms, modified by environmental cues or internal states. The mammalian body possesses a master pacemaker, which interacts with multiple other local clock mechanisms. These interactions define the temporal framework of cellular activity in practically all tissues, translated into a temporal pattern for hormonal secretion, cognitive function, intensity of metabolic reactions, immune and stress responses. Sustained dysregulation of bio-rhythmicity is associated with the process of ageing and disease development. In the light of accumulating evidence on the importance of bio-rhythmicity, an emphasis should be given to chronopharmacological concepts for improving the efficacy of various established therapeutic agents and open new pathways for novel translational research.